A cross-sectional single-centre study on the spectrum of Pompe disease, German patients: molecular analysis of the GAA gene, manifestation and genotype-phenotype correlations - Herzog, Andreas; Runz, Heiko (Orphanet journal of rare diseases, 2012)
Pompe disease (Glycogen storage disease type II, GSD II, acid alpha-glucosidase deficiency, acid maltase deficiency, OMIM # 232300) is an autosomal-recessive lysosomal storage disorder due to a deficiency of acid alpha-glucosidase (GAA, acid maltase, EC 3.2.1.20, Swiss-Prot P10253). Clinical manifestations are dominated by progressive weakness of skeletal muscle throughout the clinical spectrum. In addition, the classic infantile form is characterised by hypertrophic cardiomyopathy.